AUTHORITY CONFLICT OF ACEH’S QANUN REVIEW BETWEEN THE MINISTRY OF HOME AFFAIRS AND THE SUPREME COURT - Mizaj Iskandar Usman (al-Afkar, Journal For Islamic Studies, 2021)
This study aims to understand the conflict of authority in reviewing Aceh's Qanun between the Ministry of Home Affairs and the Supreme Court. As a special autonomous province, Aceh is the only region given the authority to formally implement sharia law. These status was legitimized by the three national laws, namely the Law of Aceh as Special Region (No. 44/1999), which was strengthened by the Law of Special Autonomy of the Province of Nanggroe Aceh Darussalam (No. 18/2001), and the Law of the Governing of Aceh (LOGA, No. 14/2006). To regulate the Aceh’s privileges and sharia’s implementation, the Aceh Government is allowed to issue a regional regulation called as a Qanun. LOGA orders the authorities to review and annul the Aceh’s Qanun. The Qanuns that are against the public interest and higher laws are examined through an executive review by the Ministry of Home Affairs. Meanwhile, the qanuns that regulate the implementation of sharia are evaluated through a judicial review by the Supreme Court. However, the Central Government regards the Qanun equal to the regional regulations in other provinces. This has led to the neglect of the privilege of Qanun as a special rule in realizing Aceh's privileges, particularly in the implementation of sharia. As such, the central government can delegate all authority to the ministry of Home Affairs in order to review and annul the Aceh’s Qanuns, referring to Law no. 5/2015 on Regional Government. As a result, it is found that there are 65 Qanuns that have been recently canceled by the Ministry of Home Affairs through an executive review mechanism.